State Grid: a inserção chinesa no setor elétrico brasileiro - Vanderlei, Gary Rainer Chumacero (2018)
This dissertation presents the results of a research on the contemporary Sino-Brazilian relations in the energy field. Based on the literature on international cooperation and strategic partnership, the study of qualitative nature collected, described and analyzed data related to the process of intensification of China's inclusion in the Brazilian power sector between the periods of 2010 and 2017. Emphasizing the case of performance of State Grid Corporation of China (SGCC) in Brazil and the acquisition of Companhia Paulista de Força e Luz S.A. (CPFL) by this company in 2017, the research aimed to understand the reasons for the Brazilian Government's permission to increase the Chinese participation in the sector and its effects on the bilateral relations in the area of energy and development of electrical industry nationally. Starting from an initial hypothesis that the positioning adopted by the Brazilian Government has been due to their interest in the maintenance of Chinese investments in the electricity sector, domestic work used the Process Tracing method to analyze the political dimensions, scientific-technological and commercial financial bilateral relations in the energy area, being the completion of the survey the existence of significant convergence between Brazilian and Chinese interests in the energy field but also the observation of a curious weakness in Sino-Brazilian current dynamics.